Exploring the Prevalence of Misconceptions Regarding Heat and Temperature among Grade Nine Natural Science Learners - Kibirige, Israel (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Learners bring various misconceptions to class. The study explored learners’ misconception prevalence about heat and temperature among Grade nine Natural Sciences learners. A single case study design with 30 Grade nine learners from one secondary school in Magatle Circuit. The Heat and Temperature Concept Questionnaire (HTCQ) was used to elicit learners’ misconceptions. For each questionnaire item, percentage frequencies of incorrect, correct, and unanswered responses were calculated. The overall prevalence of misconceptions regarding heat and temperature among learners ranged from 40 to 93% (Mean 68.0% SD = 6.3), with the highest prevalence in thermal dynamic questions. The correct responses ranged from 0 to 57% (Mean = 25.1, SD = 7.1) where most learners scored between 20-30%, while unanswered questions ranged from 0 to 13% (Mean = 6.9, SD = 1.3). These results show a high prevalence of misconceptions. They could not explain how heat travels within molecules of different objects because of the lack of a link between every knowledge and school science. The findings of this study have several implications for classroom planning, teaching, and the designing of learning materials.